The United States safe space campus controversy and the paradox of freedom of speech. Issue 1 (1st January 2016) - Pujol, Jordi
Abstract: The article examines a remarkable paradox between the overwhelming public view supporting free speech as a principle, as attested by specific polls about the issue, and the fact that most people require establishing boundaries on certain types of speech. Particularly, while American society seems to openly accept free speech and even hate speech, the new generation of America requires 'safe spaces' without offensive speech. This paradox seems to be a blow to the liberal position regarding freedom of speech, specifically to the principle of tolerance. John Milton's call for liberal tolerance based on Voltaire's enlightened conception is explored in contrast to the classical understanding.